THE ISSUE OF THE APPLICATION OF CRIMINAL LEGISLATION IN THE REPUBLIC OF UZBEKISTAN (Ustozlar uchun, 2026)
This article examines the operation and application of criminal legislation in the Republic of Uzbekistan. The importance of clearly determining the scope, principles, and mechanisms of criminal law application is analyzed, focusing on the territory and subjects of criminal legislation, as well as the challenges and modern solutions within Uzbek criminal law. The article pays attention to international experience, the legal doctrine, and the practical necessities of criminal legislation.